2017
DOI: 10.1080/01616412.2017.1281197
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative changes and neuroapoptosis induced by systemic lipopolysaccharide administration are reversed by dexmedetomidine treatment in mice

Abstract: Our results indicated that Dex could reverse neurodegenerative changes and neuroapoptosis in mice brain of septic mice induced by LPS through anti-inflammatory and antiapoptotic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 59 publications
2
46
0
Order By: Relevance
“…Numerous studies have revealed that dysfunction of the BBB may lead to brain edema, destruction of the cerebral microenvironment and subsequent brain damage (19,30). Consequently, BBB dysfunction has been proposed to represent an important factor associated with the development of PE (19,20,30). In the present study, decreased levels of EB extravasation suggested that berberine has a protective effect against BBB dysfunction.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Numerous studies have revealed that dysfunction of the BBB may lead to brain edema, destruction of the cerebral microenvironment and subsequent brain damage (19,30). Consequently, BBB dysfunction has been proposed to represent an important factor associated with the development of PE (19,20,30). In the present study, decreased levels of EB extravasation suggested that berberine has a protective effect against BBB dysfunction.…”
Section: Discussionsupporting
confidence: 49%
“…Inf lammation is an important factor involved in sepsis-associated encephalopathy, which is strongly associated with neuronal apoptosis (20,31). Another form of programmed cell death, necroptosis (32), which is strongly associated with inflammation, shares common morphological features with apoptosis and is tightly regulated by kinases, such as RIP1 and RIP3 (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, they reported that interleukin 6 levels in brain tissue are not significantly changed after 24 h. In the literature, TNF-alpha was commonly measured as a marker for sepsis associated encephalopathy in the brain tissue. The interleukin 6 levels were measured in serum [1,19,2124]. …”
Section: Discussionmentioning
confidence: 99%
“…13,14 Studies have shown that agents that control the apoptotic pathways and reduce the number of apoptotic neurons might provide a therapeutic approach against SAE. 15,16 …”
Section: Introductionmentioning
confidence: 99%